Occurrence and temporal distribution of extended-spectrum β-lactamase-producing Escherichia coli in clams from the Central Adriatic, Italy - Leoni, Francesca; Sacchini, Luca; Pieralisi, Silvia; Angelico, Gabriele; Magistrali, Chiara Francesca; Cucco, Lucilla; Massacci, Francesca Romana; Albini, Elisa; Duranti, Anna; Cammà, Cesare; Secondini, Barbara; Rinaldi, Antonio; et al. (Frontiers in Microbiology, 2023)
The spread of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli is a major public health issue. Bivalves are filter-feeder animals capable of bioaccumulating the microorganisms present in water. This physiological characteristic makes them both good indicators of environmental contamination and possible carriers of pathogenic bacteria, including those resistant to antimicrobials. The aim of this work was to investigate the occurrence of ESBL-producing E. coli in clams (n=308) collected from harvesting areas of the Central Adriatic Sea between 2018 and 2019. Overall, ESBLproducing E. coli were isolated from 3% of the samples. Of 13 ESBL-and ESBL-/ class C β-lactamase (AmpC)-producing Escherichia spp. (n= 11 E. coli, n=1 E. marmotae, n=1 E. ruysiae) isolates, 13 were resistant to ampicillin and cefotaxime, 9 to sulfamethoxazole, 6 to tetracycline and nalidixic acid, 4 to trimethoprim, 3 to ceftazidime, cefoxitin, ciprofloxacin and chloramphenicol. Moreover, the majority (8/11) of the ESBL-producing E. coli isolates were multidrug resistant. Whole genome sequencing (WGS) showed that the isolates predominantly carried blaCTX-M-15 gene (3/11) and blaCTX-M-14 and blaCTX-M-1 (2/11 each). The AmpC β-lactamase CMY-2 was found in 2 isolates. Phylogroup A was the most prevalent (5/11), followed by phylogroups D (4/11), F (1/11) and B2 (1/11). Ten different Sequence Types (ST) were identified. Occurrence at sampling sites ranged between 0% and 27%. To identify associations between the occurrence of ESBL-producing E. coli and E. coli levels, samples were divided into two groups generating results with E. coli at >230 MPN/100 g and E. coli at ≤230 MPN/100g. ESBL-producing E. coli isolates were significantly more commonly recovered in samples with higher E. coli levels (14%) than in those with lower levels of E. coli (2%). Moreover, the majority (3/4) of the potentially pathogenic strains were isolated in samples with higher E. coli levels. These findings provided evidence for the bacterial indicator of fecal contamination E. coli as an index organism for ESBL-producing E. coli isolates in bivalves.